Linear Integer Programming : Theory, Applications, Recent Developments - Munapo, Elias; Kumar, Santosh (Berlin ; Boston : De Gruyter, 2021)
This book presents the state-of-the-art methods in Linear Integer Programming, including some new algorithms and heuristic methods developed by the authors in recent years. Topics as Characteristic equation (CE), application of CE to bi-objective and multi-objective problems, Binary integer problems, Mixed-integer models, Knapsack models, Complexity reduction, Feasible-space reduction, Random search, Connected graph are also treated.
Frontmatter -- Acknowledgements -- Preface -- Contents -- About the authors -- Chapter 1 Segment search approach for the general linear integer model -- Chapter 2 Improved solution method for the 0-1 GAP model -- Chapter 3 A search for an optimal integer solution over the integer polyhedron - Two iterative approaches -- Chapter 4 Use of variable sum limits to solve the knapsack problem -- Chapter 5 The characteristic equation for linear integer programs -- Chapter 6 Random search method for integer programming -- Chapter 7 Some special linear integer models and related problems -- Chapter 8 The travelling salesman problem: Sub-tour elimination approaches and algorithms -- Index
Issued also in print.
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 02. Mai 2023)
Keywords: Integer programming; Linear programming; Operations research -- Mathematics; Integer; Nonlineare Programmierung; Operation Research; COMPUTERS / Programming / General